SCGRP: SDN‐enabled connectivity‐aware geographical routing protocol of VANETs for urban environment. Issue 5 (1st September 2017) - Venkatramana, Dharani Kumari Nooji; Srikantaiah, Shylaja Banagiri; Moodabidri, Jayalakshmi
Abstract : Vehicular ad hoc network (VANET) is a backbone of intelligent transportation system that is envisaged to play a significant role in the futuristic smart cities for safety and traffic management. Designing an optimal multi‐hop routing protocol with lower transmission delay and reduced overhead has remained to be a challenge owing to the inability of existing VANET architecture to handle scalability and flexibility efficiently. The present work incorporates an emerging network paradigm called software defined network (SDN) in VANETs. The SDN provides a global view of the network topology and includes programmability to vehicular networks. The architecture manages the complex and highly dynamic vehicular network in an abstract and simplified way by decoupling the control plane from the data plane. The work introduces a SDN‐enabled connectivity‐aware geographical routing protocol (SCGRP), a performance‐enhanced protocol for an optimised transmission of data packets. The SCGRP is simulated using MININET‐Wi‐Fi and SUMO and the results are evaluated over the existing centralised routing protocol (CRP) routing protocol to prove its better performance.